FENOMENA PERILAKU FEAR OF MISSING OUT (FOMO) DALAM PENGGUNAAAN MEDIA SOSIAL BERLEBIH PADA MAHASISWA UNIVERSITAS TRUNOJOYO - Kharisma Adzan Muhammad (PT. Media Akademik Publisher, 2024)
Internet is an information media that is most popular with Indonesian people, one of them social media, as a communication medium, is very popular with the public because of the convenience and features it offers. Now social media is developing very much rapidly proven by the presence of various kinds of social media such as Facebook, Twitter, Path, Instagram, Skype, Line, etc. To find out the phenomenon of FOMO or fear of behavior missing out in excessive use of social media among Trunojoyo University students Madura, then the method used in this research by researchers is the method qualitative reception analysis. The theory used by researchers is reception theory. Technique data collection was obtained through interviews. The objects of this research are two students psychology, Trunojoyo University, Madura. The results of this research show that the area and different student environments greatly influence how they perceive the phenomenon FOMO among Trunojoyo Madura University Students.